The Effectiveness of the TMDA Community Health Education Programme in Enhancing Awareness and Safe Use of Erectile Dysfunction Medicines - Gaudensia Simwanza; Kaanaeli Kaale (Technium Social Sciences Journal, 2026)
This study evaluated the effectiveness of the TMDA na Jamii Health Education Program in increasing awareness and promoting the rational use of erectile dysfunction (ED) medicines. Adopting a mixed-methods approach, the research pursued three objectives: (1) to assess the level of engagement with the program among ED medicine users, (2) to measure changes in users’ awareness regarding ED medicines attributable to the program, and (3) to determine the extent to which individuals apply program information in the rational use of ED medicines. Results indicated that all respondents accessed the program through various media, including ITV, Azam, TBC One, and YouTube. Higher educational attainment was associated with seeking more detailed information. Although participants generally demonstrated strong knowledge of ED causes, treatments, side effects, and misuse risks, only 23% consistently adhered to medical instructions, primarily due to a lack of steady sexual partners. Of the 120 respondents, 23% reported one year of experience using ED medicines, 19% two years, 29% three years, and 28% over three years. Regarding specific medicines, 74% reported using Sildenafil, 58% Tadalafil, 49% Vardenafil, 86% Maasai herbs, and 98% Congo dust, with many combining pharmaceutical and traditional remedies. Notably, most users were unaware of the risks associated with such combinations, reflecting a gap in the program’s content. To enhance impact, the program should expand to address traditional remedies, offer partner counseling, and specifically educate women to support ED patients. Broader educational efforts to reduce stigma and misconceptions will further empower open dialogue on men’s health and improve overall health outcomes.